Screen Time and Early Childhood Well-Being: A Systematic Literature Review Approach - Vivi Irzalinda; Melly Latifah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
The technological advancements of the 21st century have created a shift in learning experiences for children, exposing them to various digital devices from an early age. One of the keys to a prosperous future for children is knowing the impact of screen time on children's well-being. This systematic literature review aims to provide an overview of the influence of screen time on early childhood well-being from existing empirical evidence. Using the PRISMA principles, this literature review identified 23 relevant studies from scopus indexed articles (Q1-Q4). The research subjects were children and mothers. The analysis grouped themes and displayed the interconnectedness of emerging themes using VosViewer software. The results of the systematic literature review showed that generally screen time has a negative impact on early childhood well-being in the physical and psychosocial dimensions. The impact of screen time on the cognitive dimension is negative and positive. The negative impact of screen time on the cognitive dimension of early childhood well-being includes delays in early childhood language development. Meanwhile, the positive impact of screen time on the cognitive dimension of early childhood well-being is that the media and tools in learning become more interesting. The results of this literature review have implications for the importance of providing insight to various stakeholders about the impact of screen time on early childhood well-being in various conditions.